Decarboxylative ketone aldol reactions: development and mechanistic evaluation under metal-free conditions. - Blaquiere, N; Shore, D; Rousseaux, S; Fagnou, K (2009)
Malonic acid half thioesters (MAHTs) and malonic acid half oxyesters (MAHOs) are shown to undergo decarboxylative nucleophilic addition reactions with ketone and aldehyde electrophiles in the presence of stoichiometric or catalytic quantities of triethylamine at room temperature. The ability to perform these reactions under metal-free conditions has enabled a detailed mechanistic analysis of the reaction pathway leading to the (1)H NMR spectroscopic characterization of a postnucleophilic addition/predecarboxylation intermediate and experimental evidence for a reversible formation of this intermediate followed by an irreversible decarboxylation. Rate constants for each of the bond forming/bond breaking steps in the reaction pathway were also determined, casting light on the differing reactivity between MAHO and MAHT nucleophiles in these processes. Finally, the mechanistic insights gained through these studies have been employed in the development of a new decarboxylative coumarin synthesis.